Service quality attributes and students’ loyalty in influencing housing choice in South Africa - Nhlabathi, Mthobisi (Journal of African Real Estate Research, 2024)
Student accommodation has been lauded as an important aspect of student’s university experience, supporting the performance of a student during their university tenure. Using the service quality model, the study’s objective was to investigate the impact of service quality attributes on student loyalty to a particular student housing. The constructs were measured on a 5-point Likert scale, with 1 being strongly disagree and 5 being strongly agree. A total of 542 responses were collected from students residing within the Johannesburg area and analysed using SPSS version 28 and AMOS version 29. The results showed that 3 hypotheses were confirmed and 2 were rejected. Both academic and managerial implications were discussed, limitations highlighted, and recommendations made for future research. Overall, the quality of service offered by student housing will have an influence on student loyalty to that residence.